CORPORATIST AND LIBERAL DEMOCRATIC POLITICAL REPRESENTATION: DIFFERENCES AND THE POSSIBILITY OF COEXISTENCE - Gajić, Novak (Political Review, 2024)
Political representation in corporatism is discussed in this article. Corporatism is understood as an aspiration for the political structuring of society through groups constituted around their roles in society. These groups are called political corporations, while their constituting roles are most often (though not always) economic. To be corporations, these groups must be recognized both mutually and by the political system. Corporatism is also understood as action towards building such a political system. Political representation is inherent to corporatism, as a conception rooted in articulation and concertation of interests. To illustrate corporatist political representation, it is compared with liberal democratic political representation. These concepts are obviously in sharp contrast, as the former is based on group representation, while the latter is based on individual representation. It is argued here that they can still coexist – not in the spheres of political ideas and ideologies, but in the sphere of the political system. Such a system is neocorporatism (called “democratic corporatism” and “liberal corporatism” by Streek and Kenworthy), yet it can function only if corporatism recognizes the democratic state’s supremacy. Corporatism contravenes the liberal-democratic one man – one vote principle, yet it provides a range of possibilities for political representation. In neocorporatism, it is extra-parliamentary, through tripartism of labour, capital, and state. When it comes to parliamentary corporatism, it is defined by 1. number of parliamentary chambers and 2. way of decision-making. According to the number of chambers, parliamentary corporatism can be unicameral, bicameral, and multi-cameral. The two basic ways of decision-making are determined by who possesses the vote – deputies or corporations. It further branches out depending on what kind of majority is needed – simple or qualified, or the consensus of all represented corporations.